Synchrotron X-ray scattering and photon correlation spectroscopy studies on thin film morphology details and structural changes of an amorphous-crystalline brush diblock copolymer. (22nd November 2016) - Kim, Young Yong; Kim, Kyungtae; Jung, Sungmin; Kim, Changsub; Kim, Jehan; Roth, Stephan V.; Sprung, Michael; Vartanyants, Ivan A.; Ree, Moonhor
Abstract: We investigated structural details and temperature-induced structural changes of an amorphous-crystalline brush diblock copolymer, poly(3-((6-((7-(9H-carbazol-9-yl)heptanoyl)oxy)hexyl)thio)propyl glycidyl ether)60 - b -poly(glycidyl 12-((3, 3, 4, 4, 5, 5, 6, 6, 7, 7, 8, 8, 9, 9, 10, 10, 10-heptadecafluorodecyl)oxy)-12-oxododecanoate)20 (PGK60 -PGF20 ) in nanoscale thin films using synchrotron grazing incidence X-ray scattering (GIXS) and X-ray photon correlation spectroscopy (XPCS). Interestingly, the diblock copolymer was found to form a mixture of two different hexagonal cylinder structures (HEX1 and HEX2) where the PGF cylinders were aligned in the film plane. HEX1 was composed of PGF cylinders with higher population of crystals while HEX2 consisted of PGF cylinders with lower population of crystals. Surprisingly, the PGF block chains favorably self-assembled because of strong lateral interactions in the bristles, forming vertical multibilayer structure with partial interdigitation even in the highly confined cylindrical geometry. In heating run up to 340 K, some fraction of HEX2 was transformed to HEX1 via cold crystallization. In contrast, HEX1 was transformed to HEX2 above 340 K because of melting of the PGF crystals. The XPCS analysis found that the HEX structural changes associated with the cold crystallization in the PGF cylinder domains took place with relatively fast dynamics. The HEX structural changes associated with melting of the PGF crystals in the cylinder domains occurred with relatively slow dynamics; this unusual dynamics of structural changes might be attributed to a high energy melting process of PGF crystals against strong lateral interactions of the bristles. Graphical abstract: Nanoscale thin film morphology details and temperature-induced structural changes of an amorphous-crystalline brush diblock copolymer containing carbazole and fluoroalkyl end groups at the bristle ends were investigated using synchrotron X-ray scattering and photon correlation spectroscopy. Highlights: Hierarchical structure of an amorphous-crystalline brush diblock copolymer in nanoscale thin films was investigated. The crystallizable block chain makes two different hexagonal cylindrical packing orders. The fluoroalkyl containing brush block reveals strong tendency to crystallize even in confined cylindrical geometry. The fluoroalkyl containing brush block tends to undergo cold crystallization, causing a fast mode of structural changes.